The development of an Australian teacher performance assessment: lessons from the international literature. Issue 5 (19th October 2020) - Stacey, Meghan; Talbot, Debra; Buchanan, John; Mayer, Diane
ABSTRACT: The requirement for all Initial Teacher Education programs in Australia to include a capstone teacher performance assessment (TPA) is relatively new. However, TPAs are common in other countries, particularly the United States. In this article, we report on a review of the literature instigated by the authors' involvement in the development of an Australian TPA. Through a systematic review of the international research literature, supplemented by a separate set of preliminary sources, we identify and explore a range of key considerations for the development of TPAs within the Australian context. We focus on common aspects of TPAs worldwide: planning and preparation, observations on and evidence of teaching practice, and student work samples. We then interrogate further issues related to TPAs including the role of schools, principals and teachers; relation to Initial Teacher Education coursework; fairness; validity and reliability; and rubric development. To conclude we present a series of guiding principles to support the development and implementation of such complex, high stakes, and increasingly mandated kinds of assessments.